iOS Forensic Analysis for iPhone, iPad, and iPod touch - Morrissey, Sean. (Apress : Imprint: Apress, 2010)
iOS Forensic Analysis provides an in-depth look at investigative processes for the iPhone, iPod Touch, and iPad devices. The methods and procedures outlined in the book can be taken into any courtroom. With never-before-published iOS informationand data sets that are new and evolving,this book gives the examiner and investigator the knowledge to complete a full device examination that will be credible and accepted in the forensic community.